New species of Hoho, Mallacoota and Parelasmopus (Maeridae: Amphipoda) from Australian waters - Hughes, L. E. (Zootaxa, 2011)
Fourteen new species of Maeridae amphipods from tropical and temperate Australian waters, including the offshore territories of Norfolk Island, Tasman Sea; Cocos (Keeling) and Christmas Islands, Indian Ocean are described. Six new species of Hoho Lowry & Fenwick, 1983, seven new species of Mallacoota J.L. Barnard, 1972 and one new species of Parelasmopus Stebbing, 1888 are included: Hoho fenwicki sp. nov., H. kalbarri sp. nov., H. kangarooensis sp. nov., H. lowryi sp. nov., H. tricarinata sp. nov., H. wittecarra sp. nov., Mallacoota barnardi sp. nov., M. bulowara sp. nov., M. kunmunyah sp. nov., M. maridwinae sp. nov., M. penelope sp. nov., M. sirius sp. nov., M. worimi sp. nov. and Parelasmopus aumogo sp. nov., are described herein. New distributions records are provided for 14 known species including Parelasmopus dancaui Ortiz & Lalana, 1997 and Mallacoota insignis (Chevreux, 1901) which have not been recorded from Australia before.